LEGAL PROTECTION FOR INFRINGEMENT OF UNAUTHORIZED USE OF THE REGISTERED TRADEMARK SARAH GAJAH DUDUK - Aditya Yunianto; Ade Maman Suherman; Tri Setiady; Wiwin Triyunarti (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2026)
PT. Gajah Duduk is one of the largest sarong manufacturing companies in Indonesia. In carrying out its business activities, PT. Gajah Duduk uses a distinctive symbol—commonly referred to as a trademark—on its products to make them recognizable to the public. This trademark has been officially registered with the Ministry of Law and Human Rights. However, over time, PT. Prisma Abadi Jaya was found to have produced sarongs bearing a mark that closely resembled the registered Gajah Duduk trademark. Moreover, the goods in question fall under the same class of goods for which PT. Gajah Duduk holds its trademark rights. This action clearly violates statutory provisions and causes harm to the legitimate trademark holder. In response, PT. Gajah Duduk filed a lawsuit to cancel the trademark allegedly used without authorization by the other party. Given this context, it is essential to further examine the legal protection of registered trademarks in Indonesia, how unauthorized use of trademarks applies in the case of the Gajah Duduk sarong, and how PT. Gajah Duduk’s trademark rights are protected against PT. Prisma Abadi Jaya. In addition, a comparative analysis with trademark protection systems in other countries will also be discussed. This research employs a normative-juridical method, which involves analysis based on legal theories, expert opinions, legal literature, and applicable regulations. The findings of this study indicate that legal protection for trademarks in Indonesia has been established through enacted legislation and other relevant regulatory frameworks.